Spontaneous Pneumothorax: Follow up Treatment Outcome in a Tertiary Care Center of Eastern Nepal - Ghimire, R. H.; Ghimire, A.; Bista, B.; Yadav, S.; Shreewastav, R. K. (Kathmandu University Medical Journal, 2020)
Background Spontaneous pneumothorax is not an uncommon medical emergency in pulmonary practice. Related data are not available in our setting. In emergency departments, clinical presentation is often confused with other cardiopulmonary problems. Follow up outcome is important for better patient care. Objective To study clinical profile and outcome after non surgical intervention in a tertiary care center. Method This was a prospective observational study carried out in Nobel Medical College, Biratnagar over last 3 years. We enrolled consecutive spontaneous pneumothorax patients over 15 years of age. Each data related to individual patients were collected in predefined proforma. To study follow up outcome of management, we used OPD attendance or if not possible took, at least two telephone numbers from the patients. All patients were followed for recurrences. Data was statistically analyzed using SPSS software. Result Over the last 3 years, we enrolled 65 spontaneous pneumothorax patients. Secondary spontaneous pneumothorax was more common (92.3%). Commonest presentations were acute pleuritic chest pain (92.3%), dyspnea (84.62%) and cough (92.3%). COPD (46.14%), PTB sequelae (15.38%), bronchiectasis (23.07%) and bullous lung disease (23.07%) were common risk factors. Tube thoracostomy (95.38%) with pleurodesis with iodopovidone (84.61%) led to lung expansion in 92.3% cases. During follow up, only 4.61% had recurrences of pneumothorax. There was one mortality. Conclusion Spontaneous pneumothorax is a common pulmonary emergency. Meticulous and careful assessment of the patients may help reach the diagnosis even in primary care setting. Tube thoracostomy followed by pleurodesis with iodo-povidone suffices in most circumstances leading lower future recurrences.